Voter Behavior in Mitigating Money Politics during the 2022 Village Head Election in Ujung Teran Village, Karo Regency - Cindy Arliyani Br Surbakti; Muntasir Abdul Kadir; Zulham Zulham; Zulfadli Zulfadli (Journal of Politics, Governance, and Administration, 2026)
Money politics remains a persistent challenge in local electoral contests and frequently undermines democratic principles. However, the 2022 Village Head Election (Pilkades) in Ujung Teran Village presented an unusual case in which financial incentives were not the dominant factor influencing electoral outcomes. This study aims to analyze voter behavior and explain how the Karo traditional social identity system (Tutur Siwaluh) contributes to mitigating money politics. Employing a descriptive qualitative approach, data were collected through in-depth interviews with ten informants, field observations, and document analysis. The findings indicate that most community members exhibit traditional voting behavior characterized by strong kinship ties and deference to customary leaders (Kalimbubu). These local cultural values function as a form of collective moral control, generating internal sanctions through feelings of shame (mela) and the potential loss of social trust. The findings further suggest that strengthening social capital and revitalizing local wisdom may complement formal legal oversight in safeguarding electoral integrity at the grassroots level.